Analisis Kalor Jenis Dudongean: Studi Pemanfaatan dalam Pembelajaran Fisika - Dhimas Arif Nurfachri; Haeruddin Haeruddin; Ielda Paramitha; Muhammad Jarnawi; Muhammad Zaky (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
Contextual and local wisdom-based physics learning is essential to improve students' understanding and interest. This research connects abstract physics concepts with everyday life and local culture, making the material more relevant and increasing learning motivation. One example of application is the use of dudongean, a traditional clay jepa-making tool, to teach the concept of thermodynamics. This study measured the specific heat of dudongean, which was shown to have an average value of 552 J/kg°C, making it effective for cooking as it allows for even and stable heat distribution. The research method involved laboratory experiments with tools such as a digital balance, calorimeter and infrared thermometer. Results showed consistency in specific heat values, especially in the larger-mass samples, confirming the effectiveness of dudongean in cooking Japanese food. The results showed that the average specific heat of dudongean was 552 J/kg°C, with values ranging from 0.50 x 10³ J/kg°C to 0.59 x 10³ J/kg°C. This research also resulted in the development of a more interactive and contextualized Student Worksheet (LKS) for physics learning, which is expected to increase students' learning motivation, concept understanding, and critical thinking skills. This research confirms the importance of integrating local wisdom in science learning, improving the quality of physics education in Indonesia, and making a significant contribution to cultural preservation and technological innovation.